Development of Natural Science Teaching Materials (IPA) Based Outdoor Basic Learning to Improve Creative Thinking Skills of Students in Class 2 Toboali State School 4, Bangka Selatan Regency - Elly Elly; Maman Rumanta; Widiasih Widiasih (Budapest International Research and Critics University, 2021)
This study aims to develop teaching materials outside the classroom (essential outdoor learning) to increase student creativity. Teaching materials as learning resources are developed by taking the environment outside the classroom that is related to students' daily lives. Natural Sciences (IPA) teaching materials consist of Student's Books and Teacher's Books, used in class 2 elementary school (SD) Negeri 4 Toboali. This teaching material contains essential competencies about the experimental results of solid objects that do not change shape. This study uses the Research and development model Borg and Gal (2002) with nine steps. At the validation stage, it was found that the Class 2 Science Teaching Materials Based on the Outside of the Classroom and the Learning Implementation Plan (RPP) had met the element of validity with minor revisions. The formative evaluation results through 3 stages after being revised obtained input that the Out-of-Class-Based Science Teaching Materials are suitable for use in science learning for Grade 2 SD Negeri 4 Toboali. Based on the test scores, the Out-of-Class-Based Science Teaching Materials can help Class 2 students of SD Negeri 4 Toboali understand learning materials, especially in Theme 2 science learning.